Challenges to the surveillance of non-communicable diseases – a review of selected approaches - Kroll, Mareike; Phalkey, Revati K.; Kraas, Frauke (BioMed Central, 2015)
Background: The rising global burden of non-communicable diseases (NCDs) necessitates the institutionalization of surveillance systems to track trends and evaluate interventions. However, NCD surveillance capacities vary across high- and low- and middle-income countries. The objective of the review was to analyse existing literature with respect to structures of health facility-based NCD surveillance systems and the lessons low- and middle-income countries can learn in setting up and running these systems.